2005
DOI: 10.1371/journal.pbio.0030401
|View full text |Cite
|
Sign up to set email alerts
|

Impaired DNA Replication within Progenitor Cell Pools Promotes Leukemogenesis

Abstract: Impaired cell cycle progression can be paradoxically associated with increased rates of malignancies. Using retroviral transduction of bone marrow progenitors followed by transplantation into mice, we demonstrate that inhibition of hematopoietic progenitor cell proliferation impairs competition, promoting the expansion of progenitors that acquire oncogenic mutations which restore cell cycle progression. Conditions that impair DNA replication dramatically enhance the proliferative advantage provided by the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 56 publications
1
44
0
Order By: Relevance
“…Flow cytometric analyses of phosphorylated signaling proteins (37) were as performed previously, with modifications. Additional flow cytometric analyses, retroviral transduction, BMT (omitting 5-fluorouracil priming), and pathological examinations were performed as described by Bilousova et al (13). Statistical analysis was performed using GraphPad Prism 5 software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analyses of phosphorylated signaling proteins (37) were as performed previously, with modifications. Additional flow cytometric analyses, retroviral transduction, BMT (omitting 5-fluorouracil priming), and pathological examinations were performed as described by Bilousova et al (13). Statistical analysis was performed using GraphPad Prism 5 software.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that contexts of reduced cellular fitness caused by replicational stress or combined genetic disruption of E2f1 and E2f2 increase the selective advantage conferred by expression of Bcr-Abl in hematopoietic progenitors and that this increased selective advantage translates into increased leukemogenesis (13). The chromosomal translocation generating p210 Bcr-Abl is the major cause of chronic myelogenous leukemia (CML), and translocations generating p210 or p190 Bcr-Abl fusions are present in acute lymphoblastic leukemias (ALLs) (14).…”
mentioning
confidence: 99%
“…defective replication induced by aphidicolin-mediated DNA polymerase inhibition results in a high frequency of tumor-like micro-deletions; 22 hydroxyurea-induced dNTP depletion resulting in replication stress and DNA damage promotes leukemogenesis in mice. 23 Our findings show that missegregation of even a single chromosome might instigate genomic instability by elevating replication stress, which in turn might contribute to tumorigenesis.…”
Section: Aneuploidy Triggers Genomic Instability In Human Cellsmentioning
confidence: 75%
“…They demonstrated that conditions that impair DNA replication (in this case mutation of E2F1/E2F2) in haematopoietic progenitors significantly enhanced the proliferative advantage after oncogene expression or p53 mutation, while healthy replicating progenitors cells did not gain any benefit. 23 The competitive advantage allows mutant progenitors cells to outcompete wild type cells in the same niche, promoting leukemogenesis. Thus, in a replication-impaired scenario acquisition of oncogenic mutations might provide a relatively larger selective advantage.…”
Section: Aneuploidy Genomic Instability and Cancermentioning
confidence: 99%
See 1 more Smart Citation